Introducing the Sounds of Objects in Early Childhood Daily Life through a Collection of Early Childhood Fairy Tales - Zubaedah, Siti (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2024)
This study examines the use of the storybook Koleksi Dongeng PAUD: Mengenal Suara di Sekitar Kita (PAUD Storybook Collection: Recognizing Sounds Around Us) as a tool to introduce everyday sounds to young children. Using a qualitative method with a content analysis approach, the research explores the narratives and illustrations in the book, which are designed to familiarize early childhood learners with various sounds. Data analysis was conducted through three main stages: data reduction, data presentation, and data verification to understand patterns in sound recognition and their impact on children’s cognitive, emotional, and social development. The findings reveal that the book introduces two main categories of sounds, those originating from humans, such as heartbeats, humming, coughing, sneezing, growling stomachs, and chewing sounds during eating, and those from the surrounding environment, such as knocking on doors, vehicle horns, breaking objects, splashing water, ticking clocks, and bicycle bells. The book fosters children’s development by introducing sound recognition, environmental understanding, and social interaction reflection. Its stories enhance self-awareness, identity formation, and language skills. This research’s significance lies in its innovative integration of auditory learning into storytelling, promoting cognitive, emotional, and moral growth in early childhood. However, it is limited by its focus on specific sounds and the lack of empirical testing to assess long-term effectiveness. Its cultural specificity may also limit broader applicability. Future studies should explore diverse sounds, including cultural and natural environments, and examine longitudinal impacts. Cross-cultural adaptations could transform similar books into universal educational tools.